Effect of protein-phenolic acid complexes on ice cream structure and meltdown behavior - Hesti Ayuningtyas Pangastuti; Songsak Wattanachaisaereekul; Praphan Pinsirodom (LWT, 2024)
This study focused on understanding the effects of protein-phenolic acid complexes on structural changes and meltdown behavior in ice cream. Three phenolic acids (4-hydroxybenzoic acid, vanillic acid, and gallic acid) at two concentrations (2 and 10 mg/g) were individually investigated. Compared to control ice cream, 2 and 10 mg/g phenolic acid increased the induction time for the first drip by 175–200% and 200–292%, respectively. Ice cream with gallic acid and vanillic acid at 10 mg/g exhibited the lowest meltdown rates compared to other treatments. Addition of phenolic acids caused reduction of ice cream pH (4.92–6.13), overrun (23.11–69.02%), consistency coefficient (9.47–175.56 Pa s n ), and melting enthalpy (154,320–193,330 J/kg), while increasing the apparent viscosity (478.37–8770.17 mPa s), flow behavior index (0.42–0.62), and fat globule size (2.22–10.53 μm). Fluorescence spectroscopy analysis of a model ice cream mix indicated the presence of protein-phenolic acid interactions. Microscope images of ice cream samples treated with SDS and EDTA further suggested that protein-phenolic acid interactions help create fat aggregation. These findings indicate that addition of phenolic acid to an ice cream mix affects its microstructure by generating protein-phenolic acid complexes that cause protein-mediated fat aggregation, altering the ice cream's viscosity properties and resulting in a lower meltdown rate. • Incorporation of phenolic acids into ice cream resulted in lower meltdown rates. • The existence of milk protein-phenolic acid interactions was confirmed in this study. • Protein-phenolic acid complexes induce fat aggregation that affects ice cream mix viscosity and ice cream meltdown rate.
Keywords: Freezing and Crystallization Processes; Microencapsulation and Drying Processes; Meat and Animal Product Quality